2018
DOI: 10.7759/cureus.2698
|View full text |Cite
|
Sign up to set email alerts
|

Combating Scientific Misconduct: The Role of Focused Workshops in Changing Attitudes Towards Plagiarism

Abstract: IntroductionScientific misconduct is a global issue. There is low awareness among health professionals regarding plagiarism, particularly in developing countries, including Pakistan. There is no formal training in the ethical conduct of research or writing for under- and post-graduate students in the majority of medical schools in Pakistan. Internet access to published literature has made plagiarism easy. The aim of this study was to document the effectiveness of focused workshops on reducing scientific miscon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
4
9
0
1
Order By: Relevance
“…To eliminate or at least minimize plagiarism among researchers, efforts are needed to enhance creativity, establish new learning pathways, enhance writing skills, and increase awareness among researchers. A recent study by Rathore, Fatima, Farooq, and Mansoor () highlighted the need and importance of workshops for improving awareness of research ethics and reducing scientific misconduct in developing countries. The study emphasized that workshops specifically focusing on plagiarism can improve the present scenario.…”
Section: Discussionmentioning
confidence: 99%
“…To eliminate or at least minimize plagiarism among researchers, efforts are needed to enhance creativity, establish new learning pathways, enhance writing skills, and increase awareness among researchers. A recent study by Rathore, Fatima, Farooq, and Mansoor () highlighted the need and importance of workshops for improving awareness of research ethics and reducing scientific misconduct in developing countries. The study emphasized that workshops specifically focusing on plagiarism can improve the present scenario.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we found he similar significant difference among the faculty member's attitude and knowledge related to the importance of plagiarism after pre and post workshop analysis. [12][13] The study was done at one of the University of Egypt, the data was collected by the faculty members of nursing and pre and post workshop analysis was done to compare the basic knowledge regarding plagiarism. 55% of the participants were aware about the plagiarism, 58.8% of them were refusing plagiarism and 51% given incorrect answers in pretest analysis while according to post analysis there was significant difference in pre and posttest analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Others reported inadequate understanding of plagiarism among undergraduates in Pakistan (Javaeed et al, 2019;Ramzan et al, 2012;Rathore et al, 2018), Thailand (Khathayut et al, 2020), Japan (Rinnert & Kobayashi, 2005), Taiwan (Chien, 2017), and China (Hu & Lei, 2012. Limited understanding of plagiarism was also held by postgraduate students in Japan (Rinnert & Kobayashi, 2005), Iran (Rezanejad & Rezaei, 2013), Thailand (Puengpipattrakul, 2016), and Pakistan (Ramzan et al, 2012;Rathore et al, 2018). Du (2020) found that most Chinese postgraduate students possessed limited understanding of subtle plagiarism before engaging in a training section about referencing and plagiarism.…”
Section: Knowledge Of Plagiarismmentioning
confidence: 99%
“…For example, Du (2020) indicated a lack of instruction on appropriate referencing in most tertiary institutions in mainland China. Rathore et al (2018) found that many students in a Pakistani university received inadequate training on plagiarism. Limited plagiarism education was reported in Thai (Khathayut et al, 2020;Puengpipattrakul, 2016), Iranian (Babaii & Nejadghanbar, 2017;Rezanejad & Rezaei, 2013), and Japanese (Rinnert & Kobayashi, 2005) contexts.…”
Section: Plagiarism Educationmentioning
confidence: 99%
See 1 more Smart Citation